Defining the Prevalence of Molar Incisor Hypomineralization in Brazil - Fernanda Mafei Félix da Silva; Yuqiao Zhou; Fernanda Gabriela de Fátima Vieira; Flávia Martinez de Carvalho; Marcelo de Castro Costa; Alexandre Rezende Vieira (Association of Support to Oral Health Research (APESB), 2022)
Objective: To define the prevalence of Molar Incisor Hypomineralization (MIH) in Brazil since the reports ranged from 2.5% to 40.2%. Material and Methods: We studied 407 children from 7 to 14 years of age. MIH was measured using the European Academy of Paediatric Dentistry criteria of 2003. Clinical data were collected by a calibrated dentist (Kappa=0.88) and included affected  teeth  and  degree of MIH severity (mild/severe). Mild MIH cases  were  considered when the tooth presented  demarcated opacity ≥ 1.0mm, without any loss of structure. While severe cases were defined by teeth in which loss of structure was present, or past or current lesion that required treatment, or presence of atypical restorations. In addition, published data (nine studies) reporting MIH in Brazilians were identified, and the heterogeneity of these studies was tested (I2 index/ p≤0.01). Results: In the original sample studied, the majority of patients were males (55.3%; n = 225), with an average age of 10.1 years (± 2.1 years). The prevalence of MIH in this group was 14.5% (59 affected in 407), and most of the affected teeth had a mild degree of alteration (77.4% or 202 in 261 teeth). Conclusion: A meta-analysis including nine published reports, and our original data showed that MIH prevalence in Brazil is 13.48 (95% CI, 8.66% -18.31%).